2017
DOI: 10.18632/oncotarget.19805
|View full text |Cite
|
Sign up to set email alerts
|

177Lu-PSMA-617 radioligand therapy for a patient with lymph node metastatic prostate cancer

Abstract: Prostate specific membrane antigen (PSMA) is expressed in unfavorable prostate cancer. PSMA is basis for new diagnostics and theranostics. PET/CT using PSMA is more sensitive than choline PET/CT. 177Lu-PSMA radioligand therapy is mainly used for patients with end-stage prostate cancer. This report describes a patient with a third recurrence in lymph nodes. The recurrence was treated with 177Lu-PSMA radioligand therapy instead of chemotherapy with docetaxel. The effect was in part evaluated relative to that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
5
8
0
Order By: Relevance
“…These findings supported the promising results indicated in two previous papers [4, 5]. As to a previous case report [4], the present study incorporates an additional 44 patients with predominant LNM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings supported the promising results indicated in two previous papers [4, 5]. As to a previous case report [4], the present study incorporates an additional 44 patients with predominant LNM.…”
Section: Discussionsupporting
confidence: 92%
“…These findings supported the promising results indicated in two previous papers [4, 5]. As to a previous case report [4], the present study incorporates an additional 44 patients with predominant LNM. As to a previous report of 19 patients with LNM treated at the Zentralklinik Bad Berka, Germany 2017 [5], the present study reported a longer follow-up to September/October 2018 and added patients treated at an Austrian, a Turkish, and two Australian centers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…But in our review, 177 Lu-PSMA RLT was more effective than third-line treatment despite being given later in the treatment sequence for mCRPC. Correspondingly, 177 Lu-PSMA-617 RLT gave better PSA decline than abiraterone in a recent case report [ 18 ].…”
Section: Discussionmentioning
confidence: 96%
“…117 Lu-PSMA RLT is mainly used as a compassionate treatment of patients with end-stage mCRPC [ 17 ]. For a patient with only lymph node metastatic CRPC, 177 Lu-PSMA-617 RLT reduced PSA more than salvage radiotherapy and abiraterone [ 18 ]. In contrast, APCCC 2017 did not refer to 177 Lu-PSMA RLT [ 19 ].…”
Section: Introductionmentioning
confidence: 99%